Misconception Profile of Students on Static Fluid Material using the Four-Tier Diagnostic Test - Izzati, Novita Kurnia; Wasis, Wasis (Jurnal Penelitian Pendidikan Fisika, 2021)
This study aims to identify and analyze the profile of students' misconceptions on static fluid material using the four-tier diagnostic test. The sample in this study were 30 students of class XI MIPA SMA Negeri 1 Paciran. The research method used was Research and Development through two stages, namely developing a four-tier misconception diagnostic test instrument, identifying and analyzing students’ misconception based on the responses to the developed tests. The developed diagnostic test is a diagnostic test that has passed the internal validity test stage of 2 physics lecturers at the State University of Surabaya and the external validity of the content and empirical constructs, as well as the reliability of the study sample. The results showed that the internal validity of the instrument was very valid. The empirical validity of the contents of the percentage of false positives is 9.33% and false negative is 3.67%, while the empirical validity of the constructs is the value of the overall validity of the items is 0.513, based on these results it shows that the instrument is valid. The instrument reliability index was declared reliable because it had a value of rxy > rtable, namely rxy is 0.723 with rtable 0.349. The profile of students' misconceptions shows that the level of students’ misconceptions is in the medium category, with the largest misconception in the concept of hydrostatic pressure. One of the causes of misconceptions experienced by students based on students' choice of answers is the effect of the wrong intuition.